2002
DOI: 10.1007/s00417-002-0448-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic correlation in hemorrhagic age-related macular degeneration

Abstract: A large spectrum of histo-architectural lesions is recognized in hemorrhagic maculopathy. Hemorrhages do not only characteristically appear in the subretinal space or in the stroma of the neovascular tissue but also at the choroidal side of the diffuse drusen adjacent to the neovascular complex and at the choroidal side of the intra-Bruch's fibrovascular tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Subretinal blood can act as a barrier to block metabolic exchange, causing degenerative changes of the RPE and outer retina. 36 In this study, none of the following were shown to be related to visual outcomes: age, gender, subretinal haemorrhage size, duration from subretinal haemorrhage to VH, duration from VH to PPV, preoperative treatment with intravitreal bevacizumab injection, or PDT. Cases with systemic disease (DM or HTN) showed a borderline relationship (Fisher's exact test, P ¼ 0.05) with poorer visual outcomes.…”
Section: Discussionmentioning
confidence: 53%
“…Subretinal blood can act as a barrier to block metabolic exchange, causing degenerative changes of the RPE and outer retina. 36 In this study, none of the following were shown to be related to visual outcomes: age, gender, subretinal haemorrhage size, duration from subretinal haemorrhage to VH, duration from VH to PPV, preoperative treatment with intravitreal bevacizumab injection, or PDT. Cases with systemic disease (DM or HTN) showed a borderline relationship (Fisher's exact test, P ¼ 0.05) with poorer visual outcomes.…”
Section: Discussionmentioning
confidence: 53%
“…2 The optimal management of AMD-related CNV associated with LSH is still a matter of debate. 19,20 However, CNV with a hemorrhage involving an area .50% of the entire CNV lesion was specifically not included in the above-mentioned trials and we cannot assume the same efficacy in this subgroup. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The anti-VEGF technique is currently the most commonly adopted treatment of exudative AMD.…”
mentioning
confidence: 99%
“…However, submacular hemorrhage often accompanies acute severe visual loss immediately after onset [2]. Histologic reports have shown that submacular hemorrhage causes severe damage to the outer retina [16,17], and experimental reports have suggested mechanisms by which chronic damage to the photoreceptor layer occurs [18,19]. However, in addition to chronic effects, bleeding within the Submacular hemorrhage from AMD.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism remains unclear as to why a thick submacular hemorrhage can cause sudden visual loss, even when the sensory retina within the macular area is seen clearly on fundus examination [2]. Histologic reports have shown that submacular hemorrhage can cause substantial damage to the outer retina [16,17]. In experimental studies with an animal model, Glatt and Machemer [18] have reported that the photoreceptors overlying areas of the hemorrhage appear to have degenerated and exhibit pyknosis within 24 hours.…”
Section: Introductionmentioning
confidence: 99%